Nonlinear differential equations and algebraic systems - Lloyd K. Williams (International Journal of Mathematics and Mathematical Sciences)
In this paper we obtain the general solution of scalar, first-order differential equations. The method is variation of parameters with asymptotic series and the theory of partial differential equations.